Implementation of Character Education in Training Early Childhood Independence at Anugerah Ameth Early Childhood Education, TNS District, Central Maluku Regency - Sri Apriyanti Selano; Lamberthus J. Lokollo; R. Tutupary (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study was to determine the implementation of character education in training early childhood independence at Anugerah Ameth PAUD. The approach used in this research is a qualitative descriptive research approach. Through this approach, it is hoped that researchers can produce descriptive data in order to reveal the causes and processes that occur in the field. The results showed that: 1) the teacher's process of implementing character education in training children's independence at Anugerah Ameth PAUD, TNS Subdistrict, Central Maluku Regency had been well planned and implemented, 2) Efforts to train children's independence, the teacher must be a good example so that children's independent abilities can develop according to the expected results, 3) Children's independence can develop if a teacher must be patient in understanding each child's character in educating him, 4) The level of independence of children has met the specified target. This can be seen when children are able to do everything themselves